Aberrant Right Subclavian Artery and Common Carotid Trunk with High Arching Azygous Vein: A Case Report - Sapkota, Sandeep; Thakur, Binay; Khatiwada, Sagar; Tiwari, Manoj; Bhattarai, Shachee (Nepalese Journal of Cancer, 2025)
Aberrant right subclavian artery (ARSA), or arteria lusoria, is the most common congenital anomaly of the aortic arch, occurring in 0.5–2% of the population, and may be associated with other rare vascular aberrations. We report a 45-year-old male with progressive grade III dysphagia for 5 months, diagnosed with well-differentiated adenocarcinoma of the distal esophagus. Preoperative contrast-enhanced CT revealed an ARSA arising as the third branch of the aortic arch and coursing posterior to the esophagus, along with a common carotid trunk and high-arching azygos vein. The patient underwent video-assisted thoracoscopic (VATS) three-incision esophagectomy following neoadjuvant chemotherapy, with vascular anomalies noted and preserved intraoperatively. This case highlights the importance of preoperative recognition of vascular variations to avoid catastrophic complications during minimally invasive esophageal surgery.